Synthesis and Aromaticity of Benzene‐Fused Doubly N‐Confused Porphyrins. Issue 25 (20th April 2020) - Uno, Hidemitsu; Muramatsu, Kota; Hiraoka, Shogo; Tahara, Hiroyuki; Hirose, Mako; Tamura, Eidai; Shiraishi, Tatsumi; Mack, John; Kobayashi, Nagao; Mori, Shigeki; Okujima, Tetsuo; Takase, Masayoshi
Abstract: A bicyclo[2.2.2]octadiene(BCOD)‐fused bis(dipyrromethane) derivative was reacted with methylal in the presence of trifluoroacetic acid followed by oxidation with chloranil to give a doubly N‐confused phlorin derivative, which did not undergo the retro‐Diels–Alder reaction extruding an ethylene molecule on heating. In contrast, a 7‐ tert ‐butoxybicyclo[2.2.1]heptadiene(7‐BuOBCHD)‐fused bis(dipyrromethane) yielded benzene‐ring‐fused doubly N‐confused porphyrins by following similar reaction sequences. Abstract : Get confused ! Benzene‐fused doubly N‐confused porphyrins showed macrocyclic18π and weak local benzene 6π aromaticity. Protons in the narrow inner cores exchange at a rate of τ 1/2 = ca. 8.5 s (see figure).